Pengenalan Potensi Ekonomi Tanaman Porang Kepada Masyarakat Melalui Produk Batik - Hanif, Nurmarilis Auliya; Darwanto (Pusat Penerbitan LPPM ISI Bali, 2024)
Porang batik from Madiun has capital problems that make it difficult for batik to develop, such as the absence ofregeneration. In the absence of regeneration, making porang batik is still not well known by the public. So from theseproblems, you can create a porang batik design by bringing out the characters on the porang plant so that it can attractthe public to better understand the potential of the porang plant. The problem in this design is how to create porangmotifs to be better known by the public. In addition, it also cultivates the porang plant as an inspiration for motifs thatcan be realized in designs into fabrics with the cold night batik technique. The method used is the Collin ClipsonMethod as a reference and principles of art by considering aesthetic aspects, materials, techniques, functions, andmarket segments. So that it is expected to be able to solve problems in the design of these products, in order to producea product that is functional and also worth selling. This design resulted in 8 designs of batik cloth with stylized andnaturalist styles. With the results of this design, it is able to present a touch or other style in the display of motifs withthe source of the idea of porang plants. Therefore, it is expected to be able to provide awareness to the public about theimportance and economic value of the porang plant.